Pelatihan Troubleshooting Laptop Alumni SMK Se-Lombok Timur - Akbar, Taufik; Dewi, Intan Komala; Alimudin, Alimudin; Ahmadi, Ihwan (Universitas Hamzanwadi, 2022)
With the rapid development of technology, especially the development of computers, both hardware and software, users must add more knowledge to running computers. Not only operating it but also installing and troubleshooting so that later it will be more accessible when faced with obstacles. SMK alumni mainly contribute to unemployment due to very few industry-standard job opportunities. Additional skills/competencies are needed to equip the alumni, one of which is by providing Troubleshooting knowledge. Troubleshooting is solving problems with damage to Computer/Laptop hardware. This training purpose is to increase the competence of alumni to be independent or prepare for the world of work. The training method applied in this training is the lecture and practice method. The activity took place with 30 registrants and was selected based on terms and conditions; the results were that only 5 participants from SMK 3 Selong and SMK 1 Pringgabaya passed. This activity was initially carried out in June at the Lombok Center IT. The result of this training activity is that participants can assemble and install laptops and install open laptop mainboard components. Participants can measure the signal on the laptop to know the damage